2005
DOI: 10.1021/jf0481960
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Phenomena Contributing to the Formation of the Aroma of Wine during Aging in Oak Wood:  An Analytical Study

Abstract: Red wine was stored in different oak barrels or in stainless steel, and samples were taken for two years to determine 79 aroma compounds. Aging in oak affects 41 compounds. The type of wood affects 11 compounds. At least seven different processes seem to take place concurrently in aroma evolution, and five such processes, affecting 37 compounds, are linked to the oak cask. These are extraction from the wood, oxidation of wine alcohols and amino acids, microbiological formation of ethyl phenols, sorption proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 30 publications
11
87
0
2
Order By: Relevance
“…The oxidative environment inside an oak barrel also stimulates the formation of sotolon, which forms due to the oxidation of threonine. The oxidative degradation of phenylalanine and b-phenylethanol in a barrel also leads to higher concentrations of phenylacetaldehyde, reminiscent of an old oak oxidation flavour (Jarauta et al, 2005). In a study conducted by Cerdàn et al (2004), the concentrations of ethyl butyrate and ethyl octanoate decreased in red wine during a period of 18 months in barrels, while those of ethyl hexanoate and ethyl decanoate increased.…”
Section: Effect Of Oxygen On Wine Aromamentioning
confidence: 99%
“…The oxidative environment inside an oak barrel also stimulates the formation of sotolon, which forms due to the oxidation of threonine. The oxidative degradation of phenylalanine and b-phenylethanol in a barrel also leads to higher concentrations of phenylacetaldehyde, reminiscent of an old oak oxidation flavour (Jarauta et al, 2005). In a study conducted by Cerdàn et al (2004), the concentrations of ethyl butyrate and ethyl octanoate decreased in red wine during a period of 18 months in barrels, while those of ethyl hexanoate and ethyl decanoate increased.…”
Section: Effect Of Oxygen On Wine Aromamentioning
confidence: 99%
“…But the isomer cis-oak lactone was higher in cider aged with American oak chips compared to French oak chips. It has been reported that the cis-isomer has a more powerful aroma than the trans-isomer, and that American white oak is richer in the cis-isomer compared to other oak species 14,16,24 . The cis-oak lactone was detected at a higher concentration than the trans-oak lactone (Table III), and this has been previously reported by other authors for most oak species 11,19,23,30 .…”
Section: Effect Of the Geographical Origin Of Oak Chipsmentioning
confidence: 99%
“…[1] Several studies have revealed the influence of oak wood on the organoleptic properties of wines matured in oak barrels. [2][3][4][5][6] This influence is considered to be due to variations in the physical and chemical properties of oak, which mainly depend on the geographical origin and the species. [7][8][9] So far, attempts to establish correlations between the chemical properties of oak wood and the origin or species have relied on targeted analyses of selected compounds.…”
Section: Introductionmentioning
confidence: 99%